Bacillus Calmette–Guerin (BCG) vaccination to treat endometriosis. Issue 50 (8th December 2021) - Hecht, Jonathan; Suliman, Sara; Wegiel, Barbara
Abstract: Bacille Calmette-Guérin (BCG), a vaccine intended to protect against tuberculosis disease, can elicit protection against heterologous infections, and even specific types of cancer. In this mini-review, we will address the possible use of BCG as a therapeutic for endometriosis, a syndrome of chronic pelvic pain due to ectopic growth of endometrial-type tissue outside of the uterine lining. These implanted tissues cycle synchronously with menses in pre-menopausal women, generating cellular debris inciting chronic inflammation and tissue scarring leading to pelvic pain and infertility. Further, these lesions may evolve into ovarian clear cell carcinoma. We hypothesize that implantation, survival and transformation of these implants is enabled by a form of immune suppression within the peritoneum, which may be overcome by BCG vaccination.